A Panel Examination of IFRS Adoption and Financial Statement Quality: Evidence from Selected Firms in Ghana - Amankwa, Richard Fosu; Mawutor, John Kweku Mensah; Yiadom, Eric Boachie (International Journal of Accounting & Finance Review, 2020)
This study examined the effect of IFRS adoption on the quality of financial statements of selected firms on the Ghana Stock Exchange. The study used the extent of management practices as a metric for financial statement quality. The audited annual reports of the selected firms from the GSE were analyzed using a panel regression model over the period 2001-2006 and 2007-2014. The study finds the adoption of IFRS to be significantly and negatively affect earnings management practices and, thus, improves financial statement quality. On the extent of earnings management practices, the study finds a decrease in the post-adoption era as opposed to the pre-adoption era, signifying an improvement in accounting quality. The panel regression results show that adopting IFRS significantly decreases the extent of earnings management.